Contribution méthodologique pour la connaissance du rôle des acteurs locaux dans la réalisation d’un projet de territoire : le cas du projet de la réserve naturelle de Réghaia dans la zone côtière Est de l’Algérois - Mohamed Larid (Développement Durable et Territoires)
In the field of territorially management, we can see the insufficiency of analysis tools on the strategies of actors. This is even more crucial in case of the developing world, where the management and territorially administration are often dysfunctional. Better knowledge of the roles of stakeholders in the implementation of a territorial project, provides insights of the context of its implementation and guidance likely to favor its success. The logical behavior help to identify issues and key questions, to achieve the objectives and ensure the completion of actions agreed. This article reports the results of a field experiment conducted in a coastal wetland in the region of Algiers. It offers a contribution, on the methodology for collecting information on the behavior and capabilities of stakeholders in the implementation of a local project, oriented to the development and protection of an important natural heritage